Strategi Manajemen Pendidikan dalam Meningkatkan Kualitas Pembelajaran PAI di Era Digital - Maisura, Maisura; Ulandary, Yury; Murnaka, Nerru Pranuta; Azhari, Devi Syukri; Erliana, Leni; Ahyani, Edi (Indo-MathEdu Intellectuals Journal, 2023)
Education management strategies can be applied to improve the quality of Islamic Religious Education (PAI) learning in the digital era. With the development of information and communication technology, innovative approaches are needed to ensure PAI learning remains relevant and effective. This research explores the concept of education management that focuses on the use of technology in PAI teaching, exploring the potential of online platforms, mobile applications, and other digital resources. This type of research is qualitative, with a descriptive approach to analysis. The data collection method used is through observation, documentation, and interviews. Data analysis techniques through data collection, data presentation and data verification. In addition, this study also discusses the challenges that may arise during the implementation of this strategy and provides a view on the integration of technology to achieve holistic PAI learning objectives. By detailing concrete steps and case studies, this research provides practical guidance for educators and school administrators to improve the effectiveness of PAI learning in facing the dynamics of the digital era